Paper Tigers, Fences-&-Fines or Co-Management? Community conservation agreements in Indonesia's Lore Lindu National Park - Stefanie Engel; Charles Palmer; Alex Pfaff (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2010)
Protected areas may be established and maintained at the expense of local communities ('fences & fines'), although attempts to block local land use can be fruitless ('paper tigers'). Innovation in protected area policy has led to the involvement of communities in protected-area management ('co-management'). This paper aims to predict and study the emergence of such negotiated agreements to share the management of as well as the benefits from forest. First, we develop a conceptual framework for understanding roles of co-management interventions. Second, we bring to our derived hypotheses unique panel data collected from a co-management policy implemented in Lore Lindu National Park, Indonesia. The results broadly support our model predictions, although there is mixed evidence in some cases, possibly due to the fact that our relatively rough data proxies often correlate with several model parameters.
Keywords: 330; forest; protected area; park; community; property right; Indonesia